2012
DOI: 10.1111/cote.12004
|View full text |Cite
|
Sign up to set email alerts
|

Digital and conventional printing and dyeing with the natural dye annatto: optimisation and standardisation processes to meet future demands

Abstract: The plant colorant annatto was investigated to determine its potential use as a natural dye for conventional and novel textile applications. Alum was selected as a mordant. Different techniques of mordanting and a broad set of variations in the dyeing recipes were applied to achieve optimisation and an improvement in colour fastness properties. Quality control of all dyeings was performed using standard fastness tests and colour measurements. Printing of cotton fabrics was also achieved with annatto using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 27 publications
(33 reference statements)
0
20
0
3
Order By: Relevance
“…From Table is can be concluded that the hue of all samples is in the red–yellow sector of the colour circle, which is in agreement with the positive a and b values and is visually confirmed. The K / S values of the digitally printed cotton samples are satisfactory and higher than those obtained by exhaustion application of natural dyes on cotton . This can be explained by the fact that natural dyes applied from an aqueous medium generally show low affinity and thus low exhaustion, whereas natural dyes applied by digital printing are deposited as required locally on the surface of the substrate through the printing nozzle, allowing more dye on the surface of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…From Table is can be concluded that the hue of all samples is in the red–yellow sector of the colour circle, which is in agreement with the positive a and b values and is visually confirmed. The K / S values of the digitally printed cotton samples are satisfactory and higher than those obtained by exhaustion application of natural dyes on cotton . This can be explained by the fact that natural dyes applied from an aqueous medium generally show low affinity and thus low exhaustion, whereas natural dyes applied by digital printing are deposited as required locally on the surface of the substrate through the printing nozzle, allowing more dye on the surface of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in colour depth vs light fastness grades in dyeings mordanted with aluminium (), tin (), iron (), chromium (), and copper () salts . Quadrants are indicated by Roman numerals in part (a) of the figure.…”
Section: Colour Depth Changes and Light Fastness Improvementsmentioning
confidence: 99%
“…The changes in colour (lightness, brightness, and hue) vs light fastness grades in dyeings mordanted with aluminium (), tin (), iron (), chromium (), and copper () salts …”
Section: Colour Changes and Light Fastness Improvementsmentioning
confidence: 99%
“…Boyamalar; mordansız, ön-mordanlama, birlikte mordanlama ve son-mordanlama olmak üzere dört yöntem kullanarak gerçekleştirildi. Doğal boyamada yaygın olarak kullanılan mordanlar şap (AlK(SO4)2·12H2O), potasyum dikromat (K2Cr2O7), kalay (II) klorür (SnCl2·2H2O), demir sülfat (FeSO4·7H2O) ve bakır sülfat (CuSO4·5H2O) [22] olmasına rağmen, bu çalışmada, metalik mordanlar arasında en zararsız olarak kabul edilen şap ve demir sülfat mordanları kullanıldı [23,24]. Gölgede kurutulmuş kızılağaç yaprakları, saf su (1:20) ortamında soxhlet cihazı kullanılarak renksizliğe kadar ekstrakte edildi ve etken boyarmaddenin su fazına geçmesi sağlandı.…”
Section: Boyama İşlemleriunclassified